Aplicação do método lattice Boltzmann ao estudo do escoamento em canais parcialmente porosos - Meira, Rodrigo Esperança da Cunha Pimentel de (2014)
In this work, flow through a channel partially filled with solid obstacles is investigated using the lattice Boltzmann method, a numerical method based on particles collision to simulate fluid flow. The influence of parameters as porosity, number of obstacles and fluid domain height are analyzed in terms of the flow rate variations through the fluid domain. Comparison between numerical results and theoretical models based on the definition of a boundary condition for the fluid-porous interface is performed as well. It is observed that the influence of porosity and number of obstacles have opposite effects. Increasing porosity leads to a more permeable medium which favors the outflow from the porous to the fluid domain. On the other hand, increasing the number of obstacles reduces medium’s permeability, which inhibits the efflux of fluid from the porous region. As the height of the fluid domain is increased, flow rate through this region is increased as well, thus the additional flow provided by the presence of the porous material becomes less significant. Numerical results are in good agreement with a benchmark model and correlation of the associated adjustable parameter is proposed.